Niger - Rural Financial Services : Expanding Financial Access to the Rural Poor - World Bank (Washington, DC, 2013)
The main objective of this study is to identify the major impediments to access to financial services in rural areas, and provide practical recommendations to address the identified problems. The study aims to inform on rural finance policies and innovative instruments by examining both supply and demand sides including an identification of non-financial issues that restrict development of the rural financial sector. Addressing the lack of rural access to financial services in the Niger development process continues to figure prominently on the Government agenda without, however, a systematic action plan and strategy. Adopting ad hoc solutions (such as the creation of an agricultural development bank) without addressing the structural issues that limit access to financial services will, unfortunately, not yield any positive long lasting results.